2011
DOI: 10.1007/s11262-011-0668-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nonstructural protein 3 are associated with attenuation in avian coronavirus infectious bronchitis virus

Abstract: Full-length genome sequencing of pathogenic and attenuated (for chickens) avian coronavirus infectious bronchitis virus (IBV) strains of the same serotype was conducted to identify genetic differences between the pathotypes. Analysis of the consensus full-length genome for three different IBV serotypes (Ark, GA98, and Mass41) showed that passage in embryonated eggs, to attenuate the viruses for chickens, resulted in 34.75-43.66% of all the amino acid changes occurring in nsp 3 within a virus type, whereas chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
(73 reference statements)
1
24
0
2
Order By: Relevance
“…Positions were based on 1ab from IBV Beaudette strain (accession number NC_001451), and modified according to Ziebuhr (2005), with position 1 the methionine at the beginning of ORF 1a and 1ab. b Based on Phillips et al (2012). The mutations in nsp6 of VicS-del (Table 1) may have implications for the replication of this virus, which would be consistent with data from previous in vivo studies (Hewson et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Positions were based on 1ab from IBV Beaudette strain (accession number NC_001451), and modified according to Ziebuhr (2005), with position 1 the methionine at the beginning of ORF 1a and 1ab. b Based on Phillips et al (2012). The mutations in nsp6 of VicS-del (Table 1) may have implications for the replication of this virus, which would be consistent with data from previous in vivo studies (Hewson et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…The ORFs 4b and 4c have been described in IBV (Hewson et al, 2011(Hewson et al, , 2012Thor et al, 2011;Phillips et al, 2012;Bentley et al, 2013), as well as in TCoV (Cao et al, 2008), and have been synthesized in vitro (Bentley et al, 2013), but the products of these ORFs are yet to be identified in infected cells, and their function remains unknown. Both these ORFs could be identified in the VicS-v genome, but in VicS-del, 4b was divided into two smaller ORFs due to a singlenucleotide deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of KM91-like 1ab genes supports the hypothesis that they conferred more favorable biological properties to the recombinants than the QX-like 1ab genes. For example, they may have conferred efficient virus replication and extended persistence in the trachea [34]. Based on the nucleotide and amino acid sequence identities, nsp 2, 3, 4, 5, and 6 were more variable than the other nsps among the viruses (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, ArkGA P60 had SNPs in the nsp2, nsp3, and both S1 and S2 gene regions. Changes in nsp2 and nsp3, which are part of the viral replicase complex, have been shown to impact viral replication and pathogenesis [32][33][34][35][36][37][38]. In the spike gene, which is the major determinant of cell tropism and plays a role in viral attenuation [39,40], 5 amino acid changes occurred in the S1 and S2 subunits.…”
Section: Discussionmentioning
confidence: 99%